The Legal Culture to Prevent Radical Islamism by a Pesantren in Madura - Mukhlis, Mukhlis; Jufri, Muwaffiq; Arowosaiye, Yusuf Ibrahim; Garunja, Evis; Boemiya, Helmy (De Jure: Jurnal Hukum dan Syari'ah, 2024)
This study examines the strategies implemented by several pesantrens (Islamic boarding schools) in Madura to curb the proliferation of radical Islam. It aims to uncover the various approaches these Islamic boarding schools employ to combat the rise of radical Islam, which has recently gained traction in the region. Utilising empirical legal research methodologies with socio-legal and anthropo-legal frameworks, the study reveals that pesantrens are proactive in teaching students—the Santri—to reject religious radicalism. Furthermore, these institutions foster religious communities, such as koloman, kamrat, and Majelis Shalawat, which have been effective in resisting radical influences in Madura. The success of these pesantrens can be attributed to their pivotal role in enhancing legal awareness among the community, steering them away from radical ideologies. This strategic influence is anchored in their capacity to modify legal behaviours through organisational structure, social control, and cultural integration. The findings affirm the critical role of pesantrens in promoting a secure, peaceful, and religiously tolerant Indonesia, highlighting their tangible contributions to national stability.